Integration and Reorganisation of Industrial R&D: Deficits and Perspectives of Empirical Research - Christoph Grimpe (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
The combination of research and development units following a merger or an acquisition usually requires a broad and widespread integration project to ensure that a company?s innovative capabilities are carried forward into the future. Previous research has shown, however, that the combined companies tend to produce fewer innovations after the transaction than before. Based on a set of theoretical hypotheses, nine empirical studies are analysed with respect to their contribution to the research problem. The review shows substantial shortcomings in content and methodology which do not allow the hypotheses to be evaluated adequately.
Keywords: M54; M10; G34; 330; Post Merger Integration; Reorganisation; Research and Development; Literature Review; Industrielle Forschung; Fusion; Übernahme; Reorganisation; Innovation; Empirische Methode; Kritik